(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Smart grid technologies are revolutionizing the energy industry by enhancing grid reliability, improving energy efficiency, and integrating renewable energy sources. This comprehensive review explores the evolution, components, benefits, challenges, and future trends of smart grid technologies. The historical background and key milestones in smart grid development are discussed, along with an analysis of components such as advanced metering infrastructure, demand response technologies, energy storage systems, grid communication technologies, and renewable energy integration. The benefits of smart grids include improved grid reliability, enhanced energy efficiency, integration of renewable energy sources, and cost savings for utilities and consumers. However, challenges such as cybersecurity concerns, interoperability issues, and regulatory and policy challenges must be addressed. Future trends in smart grid technologies, such as blockchain, artificial intelligence, and the Internet of Things, are also examined, along with their potential impact on the energy industry. By embracing these emerging technologies and implementing effective regulatory frameworks, the energy industry can leverage smart grids to build a more sustainable and resilient energy infrastructure for the future.